Effectiveness of Blended Teaching of Problem-Based Learning (PBL) and Error-Based Learning (EBL) in Gynecology - Vargas Vera, Ramon Miguel Calixto (2024)
Objective: The objective of this study was to determine whether combined PBL-ABE teaching was effective in gynecology students. Methodology: A prospective and observational study was carried out with 200 gynecology students of the tenth semester and internships, who were randomly divided into two groups for the combined PBL-ABE system and the traditional group. Pre- and post-class surveys were conducted to assess their perceptions and experiences with the method. Results: In the pre-class questionnaire, the traditional system obtained significantly higher scores than the PBL-EBL group (75.34 vs. 70.43 and 35.43 vs. 23.34), P = 6.39x10-5). In the PBL-EBL group, basic knowledge and case analysis scores increased significantly, 72.23 vs. 68.51 and 31.23 vs. 30.24, respectively (P 0.612). The PBL-EBL group improved much more than the traditional group; the PBL-EBL saw an increase from 70.43 to 72.23 compared to the traditional one from 75.43 to 68.51. On the other hand, in terms of time spent in class, the PBL-EBL system scored significantly lower than the traditional system (P < 0.001). Conclusion: PBL together with EBL can be an effective method to improve the performance and clinical skills of medical students and interns.